Osteochondral Avulsion Fracture of the Femoral Origin of the Anterior Cruciate Ligament in an 11-Year-Old Child - Sunil Kumar Pai; Nayef Aslam Pervez; Graham Radcliffe (Case Reports in Medicine)
Although tibial end avulsions of the anterior cruciate ligament are relatively common in clinical practice, avulsions of the femoral end of this ligament are by comparison rare. We present the case of an 11-year-old boy with a bony avulsion injury, which was presumed to have arisen from the tibial insertion of the anterior cruciate ligament but turned out instead to be an osteochondral avulsion fracture of the femoral origin. This unexpected finding that was not detected during preoperative workup resulted in the first attempt at surgical fixation being aborted. The need for a second planned definitive fixation procedure emphasises the importance of combining a thorough history and examination in association with appropriate imaging in the patient workup. The patient’s definitive operative treatment and outcome are described. Although rare, surgeons (and emergency room doctors) treating such patients should include femoral end avulsion injuries of the anterior cruciate ligament in the differential diagnosis of a child presenting with an acute haemarthrosis of the knee. Furthermore, once diagnosed, early onward referral to an experienced knee surgeon is advocated.